Advanced Spanish grammar a practical guide to 100+ essential skills - Aragones, Luis; Palencia, Ramon (McGraw-Hill professional education, 2015)
What you need to know to master advanced Spanish grammar McGraw-Hill Education: Advanced Spanish Grammar guides you through this often-difficult subject, clearly explaining complex grammar ideas and giving you the practice you need to reach your language goals. Written in clear, accessible Spanish, each chapter introduces one grammar topic followed by skill-building exercises, allowing you to learn and study at your Read more...